2020
DOI: 10.3390/microorganisms8111819
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic HBV Replicative Activity Is Frequently Revealed in Anti-HBc-Positive/HBsAg-Negative Patients with HIV Infection by Highly Sensitive Molecular Assays, and Can Be Predicted by Integrating Classical and Novel Serological HBV Markers

Abstract: The anti-HBc-positive/HBsAg-negative status is frequent in HIV-infection and correlates with poor survival. Here, by highly-sensitive assays, we evaluate cryptic HBV replication and factors correlated with its detection in 81 anti-HBc-positive/HBsAg-negative HIV-infected patients. Patients were treated for >12 months with HBV-active modern combined antiretroviral-therapy (cART) and had serum HBV-DNA < 20 IU/mL by commercial Real-Time PCR. Serum HBV-DNA was quantified by droplet digital PCR, serum HBV-RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…It has been reported that HBV co-infection in HIV infected people leads to a greater risk of liver disease progression 31 , increased mortality from AIDS-related events 28 , and poor HIV replication control with combination antiretroviral treatment 32 . Recent studies revealed the importance of employing sensitive biomarkers to identify HBV replicative activity in HIV-infected individuals who test anti-HBc-positive/HBsAg-negative 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HBV co-infection in HIV infected people leads to a greater risk of liver disease progression 31 , increased mortality from AIDS-related events 28 , and poor HIV replication control with combination antiretroviral treatment 32 . Recent studies revealed the importance of employing sensitive biomarkers to identify HBV replicative activity in HIV-infected individuals who test anti-HBc-positive/HBsAg-negative 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study [ 13 ], we described how HBcAb positivity was associated with a delay in achieving virological success and more frequent virological failure in HIV/HBV-coinfected patients starting ART, and we argued that possible occasional HBV replication, common in OBI patients, could contribute to the poor control of HIV replication, as demonstrated in other viral coinfections (i.e., cytomegalovirus and hepatitis C virus). The occasional presence of detectable HBV-DNA in the blood of PLWH with OBI is widely documented [ 4 , 14 , 15 ], and in vitro studies have shown the ability of HBV to facilitate HIV replication. Twu JS and Gomez-Gonzalo M and colleagues [ 23 , 24 ] demonstrated that the HBV X gene induces HIV-1 replication and HIV-1 long terminal repeat (LTR) transcription by synergizing with the Tat protein.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent paper, we demonstrated that HBcAb positivity was associated with a delay in achieving HIV undetectability and the onset of viral rebound in HBcAb-positive PLWH after triple ART initiation [ 13 ], thus suggesting the possible contribution of transient reactivation of HBV to poor HIV control. The presence of detectable HBV-DNA was demonstrated in 15% of ART-treated HIV/HBcAb-positive patients from an Italian cohort [ 14 ], and the presence of “cryptic” HBV viremia (below 20 IU/mL of commercial tests) was demonstrated in 29% of HBcAb-positive PLWH receiving ART [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a promising biomarker is represented by anti-HBc titers. Notably, in immunocompetent anti-HBc-positive/HBsAg-negative individuals, anti-HBc titers >4 cut-off index (COI) has been associated with the presence of intrahepatic cccDNA [9], while in HIV-positive patients, anti-HBc titers >15 COI is suggestive of cryptic HBV replication [10].…”
Section: Introductionmentioning
confidence: 99%